Uniqueness of infrared asymptotics in Landau gauge Yang-Mills theory - Fischer, Christian S.; Pawlowski, Jan M. (Arxiv, 2006)
We uniquely determine the infrared asymptotics of Green functions in Landau gauge Yang-Mills theory. They have to satisfy both, Dyson-Schwinger equations and functional renormalisation group equations. Then, consistency fixes the relation between the infrared power laws of these Green functions. We discuss consequences for the interpretation of recent results from lattice QCD.
Gesehen am 06.12.2017